Wood planing properties of Australian plantation-grown Eucalypts - Belleville, Benoit; Ashley, Philip; Ozarska, Barbara (Maderas. Ciencia y Tecnología, 2016)
Planing properties of seven Australian plantation-grown eucalypts were evaluated to provide recommendations on how these species should be machined and considered for the manufacture of high quality furniture and furnishings. The surface quality produced for each species was evaluated using eight planing conditions. All species performed well producing equivalent or better results than mature traditional furniture species, and could be used for high value furniture manufacturing. Tungsten carbide cutters produced better results than high-speed steel for most eucalypts and the grinding of a small chip-breaker usually produced improving results as the size of the chip-breaker was reduced. Grain orientation did not affect the planed surfaces for some species but planing with the grain usually produced better surface. Recovery and presence of torn grain could not be related to the wood density.